Efektivitas Senam Otak Dalam Meningkatkan Konsentrasi Belajar Siswa - Bili, Lukas Dairo; Lengo, Martina Dewi (Universitas Persatuan Guru 1945 NTT, 2019)
The study aimed to know the influence of brain gymnastics on the concentration of learning and to know the difference between the study concentration of intervention groups (brain gymnastics) with the control group (conventional). This research uses the design of quasi-experiment design. The population in this study is a class XII IPA student at SMA Negeri 6 Kupang, amounting to 65 students. The sample is extracted based on the formula n = 15% x N (n = 15% x 65 = 9.75, and rounded to 10). So, the samples in this study numbered 10 students for the experimental group, and 10 for the control group. While the sampling technique used is purposive sampling. The method of data collection used in this study is waning, observation, and questionnaire. The questionnaire used for a learning concentration variable is the Army alpha. The first hypothesis test results showed that there was a brain gymnastics influence on the concentration of student learning, while the second hypothesis test results showed that there was a difference between the study concentration of interventional groups (brain gymnastics) with the control group (conventional).